A dynamic perspective on the impact of process innovation upon competitive strategies - Schroeder, Dean M. (Strategic Management Journal, 1990)
Abstract The paper lays the foundation for building a dynamic theory of the impact of process innovation upon competitive strategies. An innovation is tracked over two and a half decades to observe changing patterns in competition resulting from ongoing innovation development, emerging complementary technologies, and expanding use. The study finds that the innovation created competitive opportunities and threats for both firms that adopted it and those that did not.